The European Union in Central Asia: Balancing Competing Actors and Opportunities for the V4 Countries - Kizekova, Alica (Think Visegrad, 2019)
The European Union (EU) launched its second strategy on Central Asia in 2019, providing a framework for stronger engagement with Kazakhstan, the Kyrgyz Republic, Tajikistan, Turkmenistan and Uzbekistan. Building on previous commitments, the EU has promised to approach the region more comprehensively, work with the individual states and bring improvements to Central Asia without falling victim to accusations of ‘admonishing’ in its dialogue with the region, as has sometimes been the case historically. Its focus is also on Afghanistan, a joint priority, and a source of both instability and opportunity. Increasingly, the EU is merging resources to manage its programs for Central Asia and Afghanistan. The enhanced focus on Afghanistan, however, should not overshadow the collaboration with the Central Asian states. The EU faces a challenging political environment and a diverse presence of external powers, all competing for collaboration by bringing their own regional policy initiatives. More prominently, China, Russia and the United States opt for various forms of engagement to gain influence. The EU should seek like-minded states with which to coordinate its activities to avoid duplication. The Visegrad Group countries should support and encourage the spread of the EU’s soft power by contributing to people-to-people contacts and helping with gradual economic transformations, but also offer their expertise in specific spheres, such as academic, education and research cooperation; water management or security reforms. They should be more proactive in coordinating their activities via their own embassies or programs to help make the EU’s initiative a bigger ‘game-changer’; otherwise, the ambitions in the strategy will not be met in the near to medium future.